Challenges to Foster Resilience - MacÃƒÂas, Tania Maritza DÃƒÂaz; Barreiro, Leila MarÃƒÂa ÃƒÂlava; GarcÃƒÂa, Diana Stefani VelÃƒÂ¡squez (International Research Journal of Management, IT & Social Sciences, 2018)
The work aims to provoke critical educational reflections on the current state of the scientific-pedagogical conception of inclusive education in the university context. In this sense, we are aware of the existence of an extremely positive conceptual evolution in recent times. It is necessary to articulate new discourses and teaching practices that project and illuminate the idea that inclusive education as a permanent process of change in education and for which the development of psychological activities outlined in resilience can play an important role. The Ecuadorian higher education system has experienced, for a few years, changes of great pedagogical interest. In this framework, a whole process of generating educational policies and inclusive education is shown, taking as a framework the professors and managers of the Technical University of ManabÃ (UTM) (Ecuador), to contribute to the greater inclusive development of the said university. The main challenges for university institutions regarding fostering the resilience of the academic process are presented.